2014
DOI: 10.1007/s13197-014-1383-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 biosynthesis over waste frying sunflower oil as a cost effective and renewable substrate

Abstract: Statistical experimental designs were used to develop a medium based on waste frying sunflower oil (WFO) and other nutrient sources for production of vitamin B 12 (VB12) by Propionibacterium freudenreichii subsp. freudenreichii PTCC 1674. The production of acetic acid and propionic acid were also evaluated using the same microorganism. The amount of WFO in the media was initially optimized. The amount of 4 % w/v of oil found to be an appropriate amount for production of VB12. A Plackett Burman design was then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…In a waste frying sunflower oil-based medium, Propionibacterium freudenreichii was able to produce simultaneously vitamin B 12 , propionic acid and acetic acid. Besides WCO concentration, also dimethylbenzimidazolyl, cobalt chloride, ferrous sulfate and calcium chloride was identified as factors having significant effect on vitamin B 12 production (Hajfarajollah, Mokhtarani, Mortaheb, & Afaghi, 2015).…”
Section: Other Compoundsmentioning
confidence: 97%
See 1 more Smart Citation
“…In a waste frying sunflower oil-based medium, Propionibacterium freudenreichii was able to produce simultaneously vitamin B 12 , propionic acid and acetic acid. Besides WCO concentration, also dimethylbenzimidazolyl, cobalt chloride, ferrous sulfate and calcium chloride was identified as factors having significant effect on vitamin B 12 production (Hajfarajollah, Mokhtarani, Mortaheb, & Afaghi, 2015).…”
Section: Other Compoundsmentioning
confidence: 97%
“…Despite the undesired substances produced during food frying, which may have an adverse impact on the environment and human health, this cooking process is increasingly popular (Hanisah, Kumar, & Tajul, 2013) since deep frying enhances the sensorial properties (unique fried flavor, golden brown color and crispy texture). As the use of vegetable oils on food frying should not be prolonged, an accumulation of WCO is inevitable (Nayak et al, 2016).…”
mentioning
confidence: 99%
“…For a good statistical model, the R 2 value should also be close to 1.0 where a value of 0.7 indicates the weakness of the model. 18 The value of the correlation coefficient, R 2 (93.89%) showed that the regression model provides an accurate description of the experimental data. A reasonable agreement between predicted (85.40%) and adjusted (88.55%) was also observed.…”
Section: Optimization Of Culture Conditionmentioning
confidence: 97%
“…These substrates are available in huge amounts, have very low added values, but are nutrient-rich for microbial growth (carbohydrates, proteins, and minerals). [13][14][15][16] One residue of particular interest in this case is the liquid acid protein residue of soybean (LAPRS), which is obtained as an effluent during the soybean-isolated protein process (SIP). For instance, one single industrial facility for SIP production generates approximately 50,000 m 3 of LAPRS monthly.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting factor regarding the use of this microorganism is the possibility of producing vitamin B12 using alternative culture media composed of agroindustry residues. These substrates are available in huge amounts, have very low added values, but are nutrient‐rich for microbial growth (carbohydrates, proteins, and minerals) 13‐16 . One residue of particular interest in this case is the liquid acid protein residue of soybean (LAPRS), which is obtained as an effluent during the soybean‐isolated protein process (SIP).…”
Section: Introductionmentioning
confidence: 99%